Pathogenesis of Dental Caries in Stunting - Miftah Tri Abadi; Abral Abral (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2020)
The results of the 2018 Riskesdas show that some health problems that are still major health problems in Indonesia are the high prevalence of stunting and the prevalence of cavities or dental caries. Therefore, it is necessary to further study the relationship between the two diseases to find out their pathogenesis. In general, this study aims to determine the pattern or pattern of dental caries in stunting sufferers based on the division of sextants. While the specific goal is to determine the close relationship of risk factors for dental caries index in stunting sufferers. This type of research is a non-experimental research with cross sectional design. The study was conducted in the city of Pontianak in 2019 with the research subjects being stunting toddlers. The number of research samples is 30 children, taken randomly. Retrieval of data is done by checking and interviewing his parents. Data analysis was performed by means of analysis using descriptive analysis and Pearson correlation analysis with a significance level of α = 0.05. The results of this study indicate that the sequence of sextan in the occurrence of caries in patients with stunting in a sequence are sextant II, sextant VI, sextant, IV, sextant III, sextant I, and finally sextant V. In addition, the results of the study also showed a significant relationship between risk factors for the def-T index, namely salivary pH factors (r = -0.444, Sig = 0.013), eating habits cariogenic foods (r = -0.444, Sig = 0.013), milk type factors (r = 0.520, Sig = 0.003), toothbrush factors (r = 0.654, Sig = 0.000), and debris index factors (r = 0.447, Sig = 0.013) with a degree of significance α = 0.05. The conclusion of the study was the existence of a certain pattern of dental caries in stunting sufferers and a significant relationship between risk factors and caries index in stunting sufferers.